2013
DOI: 10.1002/uog.12478
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fetal cardiac axis between 8 and 15 weeks' gestation

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…13 It has been demonstrated that cardiac axis measurement in early gestation is feasible using either the transabdominal or transvaginal approach (or both). 10,11 There has been some discrepancy in the reported data on the normal values of the cardiac axis in early gestation. This discrepancy may be explained by the relatively small number of cases in earlier studies, the technical difficulties or limited resolution of cardiac imaging before 12 weeks of gestation, and differences in Unauthorized reproduction of this article is prohibited.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…13 It has been demonstrated that cardiac axis measurement in early gestation is feasible using either the transabdominal or transvaginal approach (or both). 10,11 There has been some discrepancy in the reported data on the normal values of the cardiac axis in early gestation. This discrepancy may be explained by the relatively small number of cases in earlier studies, the technical difficulties or limited resolution of cardiac imaging before 12 weeks of gestation, and differences in Unauthorized reproduction of this article is prohibited.…”
Section: Discussionmentioning
confidence: 85%
“…14 Similar criteria were used to define abnormal axis in small series of 10 fetuses diagnosed with congenital heart disease between 12 and 15 weeks of gestation. 11 In our study, we defined normal cardiac axis as at least 30°but less than 60°. In addition, three types of cardiac axis abnormalities were suggested including left axis deviation, right axis deviation, and nonidentifiable cardiac axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormalities of cardiac axis (defined as a shift in the major axis of the heart) may occur to the right (dextrocardia), the midline (mesocardia), or to the extreme left . This measure has been shown to be established as early as 12 weeks of gestation . Cardiac axis malformations may occur as a result of intrathoracic masses, lung hypoplasia, or in association with CHD .…”
Section: Introductionmentioning
confidence: 99%
“…Fetuses with cardiac defects might show an abnormal deviation of the cardiac axis. McBrien et al [29] reported that in early gestation the cardiac axis is oriented more to the midline of the thorax and then rotates to the left, changing from 39° at 11 weeks to 50° at 14 weeks. Sinkovskaya et al [30] reported a normal variation in the cardiac axis from 34.5° at 11 weeks to 56.8° at 13 + 6 weeks of gestation, and that an abnormal cardiac axis can be associated with coarctation of the aorta, Ebstein's anomaly, transposition of the great vessels, and heterotaxy.…”
Section: Ultrasound Findings Suggestive Of Fetal Cardiac Anomaliesmentioning
confidence: 99%